Negative Emotions and Rationality of Decision-Making - Głos, Aleksandra; Załuski, Wojciech (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
The paper provides an analysis of the impact of negative emotions on decision-making processes. It questions the common-sense view that negative emotions diminish rationality of decisions, i.e., increase the probability of making suboptimal choices. It is argued in the paper that this view is untenable on the grounds of neuroscience, cognitive science and evolutionary theory: the results provided by these sciences support the view that negative emotions in most instances of their occurrence, i.e. types of negative emotions, not only fail to undermine rationality of decision-making but substantially contribute to it. This does mean saying that token-negative emotions never undermine rationality of decision-making. But, as is argued in the paper, the fact that token-negative emotions may have sometimes this kind of negative effect is fully consistent with the claim that, as a rule, the effect is positive, so that one can speak about the causal connection between types of negative emotion and rational decision-making.